Kekerasan Terhadap Perempuan Dalam Novel Mimi Lan Mintuna Karya Remy Sylado - Sara Laras Wati; Harjito Harjito; Ika Septiana (Jurnal Ragam Pengabdian, 2026)
Human trafficking is one of the most severe forms of gender-based violence, exposing women to physical, psychological, sexual, and economic abuse. Literary works often portray these realities while criticizing social injustice against women. This study aims to analyze the forms of violence experienced by the female protagonist, Indayati Sri Utamawati, in Mimi lan Mintuna by Remy Sylado. A qualitative descriptive approach with feminist literary criticism was employed. The primary data source was the novel, while data were collected through close reading, note-taking, and documentation. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, with theoretical triangulation ensuring validity. The findings reveal that Indayati experiences interconnected forms of violence throughout the narrative. Physical violence includes assault and confinement; psychological violence involves intimidation, manipulation, threats, and humiliation; sexual violence includes forced nudity, sexual exploitation, pornography, and prostitution; while economic violence appears through labor exploitation, commodification of the female body, deprivation of economic autonomy, and appropriation of the victim's labor. These findings demonstrate how patriarchal power relations and human trafficking systematically deprive women of dignity, autonomy, and fundamental human rights.